A cross-sectional audit of distress in patients undergoing adjuvant therapy or follow-up in central nervous system malignancies. Issue 4 (19th November 2018) - Patil, Vijay M; Malhotra, Mridul; Tonse, Raees; Deodhar, Jayita; Chandrasekharan, Arun; Pande, Nikhil; Bhattacharjee, Atanu; Jalali, Rakesh
Abstract: Background: Unaddressed high distress leads to noncompliance with treatment, negatively affects quality of life, and may also have a negative impact on the prognosis of cancer patients. Patients with brain tumors have higher levels of distress than the general population and hence we hypothesize that even routine visits during adjuvant treatment or follow-up are likely to be stressful. This analysis was performed to identify the incidence of distress and factors affecting it. Methods: This was an audit of 84 consecutive patients seen in an adult neuro-medical oncology outpatient department who were either receiving adjuvant chemotherapy or were on follow-up. Distress screening with the National Comprehensive Cancer Network (NCCN) distress thermometer was performed. Patients in whom distress was scored as 4 or above were considered as having high distress. Descriptive statistics and logistic regression analysis were performed to identify factors affecting distress. Results: The median age of the cohort was 40 years (interquartile range, 28.3 to 50 years). Actionable distress defined as a distress score of 4 or more was seen in 52 patients (61.9%, 95% CI 51.2% to 71.5%). Presence of physical deficit (odds ratio [OR] = 3.412, P = .020) and treatment under the private category (OR = 5.273, P = .003) had higher odds of having high distress. Conclusion: A high proportion of brain tumor patients either on adjuvant chemotherapy or on follow-up have high distress levels that need to be addressed even during follow-up.